Challenges and optimal strategies of CAR T therapy for hematological malignancies. Issue 3 (5th February 2023) - Zhang, Yajing; Xu, Yang; Dang, Xiuyong; Zhu, Zeyu; Qian, Wenbin; Liang, Aibin; Han, Weidong
Abstract : Abstract: Remarkable improvement relative to traditional approaches in the treatment of hematological malignancies by chimeric antigen receptor (CAR) T-cell therapy has promoted sequential approvals of eight commercial CAR T products within last 5 years. Although CAR T cells' productization is now rapidly boosting their extensive clinical application in real-world patients, the limitation of their clinical efficacy and related toxicities inspire further optimization of CAR structure and substantial development of innovative trials in various scenarios. Herein, we first summarized the current status and major progress in CAR T therapy for hematological malignancies, then described crucial factors which possibly compromise the clinical efficacies of CAR T cells, such as CAR T cell exhaustion and loss of antigen, and finally, we discussed the potential optimization strategies to tackle the challenges in the field of CAR T therapy.